Analisis Value Terhadap Minat Penggunaan OVO di Malang Raya Menggunakan Consumption Value Model - Nabila Aulia Anwar; Yusi Tyroni Mursityo; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This study aims to determine the values of the interest in the use of OVO in Malang partially and using multiple linear regression analysis on five variables, namely functional values, emotional values, epistemic values, conditional values and social values. The technique of collecting data using questionnaires distributed online. The population in this study is the OVO users in Malang.The sampling technique in this research is non-probability sampling using purposive sampling techniques, while samples used were 97 respondents. Based on the analysis of the partial, variable functional values have a value of t count 2.578, conditional values have a value of t count 2.340 and social values have a value of t count 2.535 significantly affect the interest of the use of OVO in Malang, while emotional values have a value of t count 1.005 and epistemic values have a value of t count 0.988 not significantly affect the interest of the use of OVO in Malang. Of the five variables can be known that which has significant influence on the interest in the use of OVO in Malang is a functional variable values. Where the use of OVO in Malang significantly affect the interest of the use of OVO in Malang for OVO services can be used to do anything and OVO has a unique service that is not owned by similar products.